2012
DOI: 10.1103/physrevb.85.060501
|View full text |Cite
|
Sign up to set email alerts
|

Quasiclassical and ultraquantum decay of superfluid turbulence

Abstract: We address the question which, after a decade-long discussion, still remains open: what is the nature of the ultraquantum regime of decay of quantum turbulence? The model developed in this work reproduces both the ultraquantum and the quasiclassical decay regimes and explains their hydrodynamical natures. In the case where turbulence is generated by forcing at some intermediate lengthscale, e.g. by the beam of vortex rings in the experiment of Walmsley and Golov [Phys. Rev. Lett. 100, 245301 (2008)], we expla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
51
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 25 publications
9
51
0
Order By: Relevance
“…The main experimental evidence (26,66) is that, if the vortex tangle is left to decay, the vortex line density decreases as L ∼ t −1 , in agreement with a phenomenological model of Vinen (7), which indeed assumes a random, homogeneous, and isotropic vortex configuration. The same L ∼ t −1 decay has been observed in numerical simulations (67), which also confirmed that the energy spectrum remains broadly concentrated near k ≈ 1=ℓ.…”
Section: Types and Regimes Of Quantum Turbulencesupporting
confidence: 73%
“…The main experimental evidence (26,66) is that, if the vortex tangle is left to decay, the vortex line density decreases as L ∼ t −1 , in agreement with a phenomenological model of Vinen (7), which indeed assumes a random, homogeneous, and isotropic vortex configuration. The same L ∼ t −1 decay has been observed in numerical simulations (67), which also confirmed that the energy spectrum remains broadly concentrated near k ≈ 1=ℓ.…”
Section: Types and Regimes Of Quantum Turbulencesupporting
confidence: 73%
“…Models based on this property describe fairly well the pioneering experiments of Vinen 6 , in which an applied heat flux drives the superfluid and the normal fluid in opposite directions (thermal counterflow). More recently, such 'Vinen' tangles were created at very low temperatures by short injections of ions 7 , exhibiting the characteristic decay L ∼ t −1/2 predicted by Vinen 8 . Under different conditions, however, the experimental evidence is consistent with a more structured vortex tangle 4,9 , where the kinetic energy is distributed over a range of length scales according to the same Kolmogorov law which governs ordinary turbulence.…”
Section: Introductionmentioning
confidence: 96%
“…The way in which this type of turbulence evolves and decays is of great interest (see, for example, ref. 41). …”
Section: Vibrating Gridsmentioning
confidence: 99%